ELECTROCHEMICAL SYNTHESIS AND PERSPECTIVES OF APPLICATION OF PEROXOCARBONIC SOLUTION FOR DISINFECTION - Châu, Nguyễn Hoài; Hà, Nguyễn Văn; Bưu, Ngô Quốc (Vietnam Journal of Science and Technology, 2012)
SUMMARYSTEL-PEROX is the latest model among the series of well-known STEL devices which produce electrochemically activated (ECA) solutions widely used for disinfection in many countries over world, including Vietnam. STEL-PEROX devices stand out as the most effective and environmentally-friendly means against microbes by generating activeted percarbonic acid from highly diluted sodium carbonate solution. Physico-chemical and functional characteristics of ECA solutions generated on a STEL-PEROX device designed and set up in Institute of Envonmental Technology-VAST using Russian electrolytic moduls FEM-3 have been evaluated. It was shown that this device  produces actually non-toxic solutions but highly effective disinfectants that destroy all forms of pathogenous microorganisms, including Salmonella, E-coli, Listeria, fungi etc, in very short contact times.  The experimental data showed that the low general mineralization of the anolyte PEROX provides a high stability of the molecular complexes which are hydrated, transforming into electroneutral aquacomplexes. That means that the lower the concentration of ions in solution, the greater the stability of the aquacomplexes, hence the longer the bactericidal activity of the anolyte PEROX.